CYCLIC FLUCTUATIONS AND SAVINGS - V. Kuligin (Вестник университета)
The duality of process of accumulation, representing saving of money, behind which there are natural and material elements of the productive capital has been considered. At limitation of resources the volume of savings can be increased only by reduction of current expenses. The consequences of credit expansion, which are not supported by voluntary savings, have been analyzed. Communication between inflation and distortion of production structure of economy has been traced. Relationship of the arising disproportions and deflation has been revealed. The conclusion has been made about violation of unity of monetary and commodity flows as main reason of cyclic fluctuations.